Metarhizium anisopliae (Metchnikoff)SorokinEffect of fungus Metarhizum anisopliae (Metchnikoff) Sorokin and actelic insecticide in pupa ages of 24 and 120 hours of Callosobruchus maculatus Fab. (Coleoptera : Bruchidae) - Baghdad Science Journal (مجلة بغداد للعلوم)
This study was perform to defined the effect of fungus Metarhizium anisopliae Sorokin with concentrations 5x101, 5x103 and 5x105 spore/ ml and Actelic insecticide with concentration 0.001% in pupa stages of Callosobruchus maculatus in pupa ages of 24 and 120 hours the results of the study showed the following: the highest killing rate of treated pupa in age 120 hours 100% at concentration 105 spore/ ml. observation for distortions in the adult insects from the pupa that treated with fungal concentration like wings and abdominal distortion , the concentration of fungal effect on the number of eggs that production from adults and percentage of hatching.